Internalized Homophobia and Self - esteem among Sexual Minority Women in Vietnam - Tran Thi Minh Duc; Ha Kieu Oanh (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
The purpose of this study is to assess the association between internalized homophobia, and self-esteem among sexual minority women in Vietnam. In this study, two key scales to measure those factors were applied, the Rosenberg Self-esteem Scale (1995) and the Internalized Homophobia Inventory (Nguyen et al. 2016). Through an online survey, we collected a sample of 302 women. The participants self-identified as lesbian, bisexual, or other sexual minority women, and had an average age of 21.23. The results indicated that there were significant distinctions among four groups which had sexual interactions with varies partners (only male, only female, male and female, no partners). The study also found that internalized homophobia and self-esteem had a negative correlation in sexual minority women. Two out three factors of internalized homophobia, “sexual minority is not normal” and “self-reproach and wish heterosexism”, which were merged in sexual self-stigma, negatively impacted self-esteem. In contrast, the remaining portion (“sexual prejudice”) did not affect this factor. Received 11th May 2020; Revised 4th July 2020; Accepted 25th September 2020